Pengaruh Public Service Motivation terhadap Kinerja Asn dengan Mediasi Jabatan Fungsional: Bukti dari BPS Provinsi Sumatera Utara - Lely Kustinova Samosir; Iqbal Miftakhul Mujtahid; Tunggul Sihombing (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of Public Service Motivation (PSM) on the performance of State Civil Apparatus (ASN) by considering the role of functional positions as a mediating variable in ASN at the Central Statistics Agency (BPS) of North Sumatra Province. The research method used was a quantitative approach with an explanatory design. Data were collected through a survey using a structured questionnaire measured on a Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS 4. The results showed that PSM had a positive and significant effect on functional positions (β = 0.636; p < 0.001), PSM had a positive and significant effect on ASN performance (β = 0.660; p < 0.001), and functional positions had a positive and significant effect on ASN performance (β = 0.257; p = 0.001). Testing for indirect effects indicates that functional positions partially mediate the influence of PSM on ASN performance (β = 0.163; p = 0.001). Furthermore, the research model has strong explanatory power, with an R² value of 0.716 for the ASN performance variable. The conclusion of this study is that Public Service Motivation is the primary factor driving improved ASN performance, both directly and through institutional mechanisms such as functional positions. Therefore, strengthening public service motivation and optimizing the functional position system need to be synergistically implemented to improve the performance of public sector organizations.  Keywords: Public Service Motivation, ASN Performance, Functional Position, Mediation